Infiltrative rectal adenocarcinoma in a dog - Paredes, Laura Jamille Argolo; Bernal, Marcella Katheryne Marques; da Gama Barbosa Monger, Suellen; Bertolo, Paulo Henrique Leal [UNESP]; de Oliveira Vasconcelos, Rosemeri [UNESP]; Pereira, Washington Luiz Assunção (Universidade Federal do Rio Grande do Sul, 2019)
Background: Intestinal neoplasms are uncommon in dogs and adenocarcinoma is the main histological type found. This neoplasm presents slow growth and high capacity of causing metastasis. Histologically speaking, neoplasm cells can present solid, tubular, papillary arrangement and note amorphous extra-cellular material. Clinically observed tenesmus, diarrhea, dyskinesia, hematochezia, mane, protrusion of the anus, weight loss, anorexia. The occurrence and clinicopathological aspects of tumors in dogs' gastrointestinal tract, the rectal segment, remains poorly understood. Accordingly, the aim of the present study is to report a case on infiltrative rectal adenocarcinoma diagnosed in a dog. Case: A 7-year-old male dog representative of the Fila Brasileiro breed was presented to the Veterinary Hospital of University Federal Rural of Amazonia, with history of hyperthermia, anorexia, apathy and tenesmus. Imaging examinations depicted prostatomegaly. Exploratory laparotomy was performed and showed the thickening and hardening of the rectum segment. The animal was subjected to euthanasia. Necroscopy showed increased rectal perimeter; the mucosa in its opening presented atypical cerebroid aspect and irregular surface, and areas dark red. The rectal segment depicted a thick wall of white color, irregular limits covering the muscular and adjacent sub-mucosa. The peri-rectal adipose tissue presented poor delimitation with the rectum, multiple greyish and reddish areas. Increased prostate and iliac lymph, and multi node of regular limits in the lungs. The histology of the rectal tissue depicted epithelium with differentiated neoformation, composed of atypical cells; nuclear anisocytosis, anisocariasis and hyperchromasia placed in small islands, cords or tubular formation. Neoplasm growth was unorganized and of infiltrative character. Some areas presented mucosal pattern cells with Signal Ring morphologic. Multiple rectal blood vessels, regional lymph nodes and lungs had neoplasm growth similar to that observed in the intestine. Mucosa also presented ulceration areas and lymphoplasmacytic infiltrate. There was fibroplasia, lymphoplasmacytic points and bleeding in the serous, as well as in the peri-rectal fat tissue. The immunohistochemical technique showed immunostaining in cytokeratin and vimentin antibodies, and in marked epithelial cells and tumor stroma markings, respectively. Discussion: The intestinal tumor diagnosis in dogs is found by associating history, clinical signs, radiographic, ultrasound findings and necropsty. Only one data about the occurrence of rectal adenocarcinoma in Fila Brasileiro specimens. With regards to sex, results were similar to those record, whose males presented higher prevalence of primary rectal tumors. The macroscopic characteristic is consistent with infiltrative neoplasms; thickening was related to the presence of the tumor. The histopathological findings evidenced growing infiltrative neoplasm formed by atypical cells of tubular arrangement. Microscopy featured a chronic ulcerative colitis frame, such alteration represents one of the main risk factors for colon rectal cancer in humans. Epithelial histogenesis was confirmed through immunohistochemical results that have revealed co-expression of the cytokine epithelial marker in most tumor cells. The vimentin mesenchymal marker in the neoplasm stroma was positive, fact that can be explained by occasional immune-reaction in the anti-bodies (cytokine and vimentin) and in non-differentiated carcinomas. The prognostic was negative in the current report. Such outcome was attributed to the infiltrative character observed in the trans-operative period. Necropsy, as well as the histopathological and immunohistochemical exams, confirmed the infiltrative rectal adenocarcinoma in the dog.
Keywords: Adenocarcinoma; Dog; Intestinal neoplasm; Rectum